In Vitro Anti-bacterial Activities of Aqueous, Ethanol and Chloroform Crude Extracts of Olinia rochetiana and Vernonia myriantha - Gashaw Nigussie; Ayana Erdedo; Sintayehu Ashenafi (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2020)
In the past with the advent of antibiotics, bacterial diseases have been under control. However rapid spread of antibiotic-resistant this success is reversing and searching for newer antibacterial agents is currently a top priority. This study was, thus, aimed at assessing the anti-microbial activities of two traditional medicinal plants: Vernonia myriantha and Olinia rochetiana. The crude extracts were tested for their in vitro antibacterial activities and phytochemical content. The extracts were tested against selected 3 clinical and 4 standard test bacterial strains by using agar well-diffusion method and the minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC). The ethanol leaves and stem-bark extracts of O. rochetiana inhibited the growth of all bacterial strains at a concentration of 250mg/mL. The inhibition zones ranged from 20.33±0.57mm for clinical Pseudomonas aeruginosa to 25.66±0.57mm for standard Salmonella typhi strains. The values for these same extracts were 20.66±2.51mm and 24.33±1.15mm for standard P. aeruginosa and Staphylococcus aureus strains respectively. The chloroform extract was similarly effective against all of the strains with inhibition zones between 19.00±1.73mm against P. aeruginosa and 22.66±2.51mm for S. aureus. Comparatively, the ethanol extract of O. rochetiana had the highest MIC (7.81mg/mL) and MBC (62.50mg/mL) were noted against P. aeruginosa. On the other hand, chloroform extract of O. rochetiana leaf showed the highest MIC (15mg/mL) and MBC (125mg/mL) were recorded against P. aeruginosa. The ethanol extract of V. myriantha showed growth inhibition only on S. aureus (21.00±1.7mm). Both plants tested for terpenoids and glycosides showed positive result, but none for resin.